2015
DOI: 10.1007/s11357-015-9841-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training with different frequencies and detraining on muscular strength and oxidative stress biomarkers in older women

Abstract: The aim of this study was to compare the effect of resistance training (RT) performed with different frequencies followed by a detraining period on muscular strength and oxidative stress (OS) biomarkers in older women. Twenty-seven physically independent women (68.8±4.8 years, 69.1±14.3 kg, 156.0±6.5 cm, and 28.3±4.9 to kg.m −2 ) were randomly assigned to perform a RT program for 2 or 3 days per week (G2X=13 vs. G3X=14) for 12 weeks followed by 12 weeks of detraining period. One repetition maximum (1RM) tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 40 publications
2
47
0
3
Order By: Relevance
“…Probably, a higher volume resistance exercise session would be needed to evoke a more pronounced acute physiological response that would make evident a protective effect (if some) of the supplementation. Secondly, participants were resistance trained, and it is known that inflammation and exercise induced muscle damage are of a less magnitude in this situation compared to unaccustomed exercise [9,10]. Of note, participants did their habitual resistance training sessions during the supplementation period.…”
Section: Resultsmentioning
confidence: 99%
“…Probably, a higher volume resistance exercise session would be needed to evoke a more pronounced acute physiological response that would make evident a protective effect (if some) of the supplementation. Secondly, participants were resistance trained, and it is known that inflammation and exercise induced muscle damage are of a less magnitude in this situation compared to unaccustomed exercise [9,10]. Of note, participants did their habitual resistance training sessions during the supplementation period.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, chronic oxidative stress, which is associated with a higher risk for depression (Diniz et al, 2018;Maurya et al, 2016) and other chronic conditions (Barnes, 2015;Quiñonez-Flores et al, 2016) may play a role. It is known that resistance training lowers oxidative stress (Franzke et al, 2018;Padilha et al, 2015;Ribeiro et al, 2017), although evidence that this also clarifies the antidepressant effects of exercise is to the best of our knowledge currently lacking (Schuch et al, 2016a). Nonetheless, the relationship between muscular strength with overall neurological health and brain function has recently been confirmed by population-scale studies demonstrating that greater handgrip strength is positively associated with greater white-matter integrity, hippocampal volume, and neurocognitive functioning in the general population, and in people with major depression (Stubbs et al, in press;Firth et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Resistance training (RT) may promote improvements in these aforementioned conditions, with positive impacts on body composition, 20,21 inflammation, 20,21 and oxidative stress biomarkers. 22 For example, Prestes et al 23 analyzed the effect of 16 weeks of RT on inflammatory markers in postmenopausal women, and results showed significant improvements in IL-6. Onabelé-Person et al 24 found a reduction in TNF-α after 12 weeks of RT program in older adults.…”
Section: Introductionmentioning
confidence: 99%